Study uropepsina in normal and pathological - Guzmán Barrón, Alberto (1954)
We have studied the time uropepsina concentration in men and having obtained an average of 32 units and 19 women, all normal. The study of the enzyme in gastric and duodenal ulcers give higher results than the normal average, gastric neoplasms in the figures are low, but as individual variations are large, it is doubtful that this determination can provide clinical utility, replacing tubaje gastric. Studying in gastrectomized uropepsina reveals that partial ulcer or cancer concentration decreases. In the total gastrectomy uropepsina disappears. In anemia with achlorhydria gastric juice enzyme research pays great diagnostic value; in pernicious anemia uropepsina is absent in the other, including aplastic hasy decline. The use of adrenocorticotropic hormone (ACTH) and cortisone in excretion study provides valuable services uropepsina. In normal subjects, administration of 25 mg regimen. of A.C.T.H. we obtained a 100% increase in the excretion of uropepsina. In cases of pernicious anemia the A.C.T.H. or cortisone are able to appear in the urine enzyme but other anemias increase is similar to that of normal subjects. Addison's disease ACTH administration uropepsina fails to increase, but in these cases the administration of cortisone increases the excretion of the enzyme, and we believe it represents an easy test to be performed, for diagnostic purposes. Given the simplicity of the method and useful services that can be provided, we believe that the determination of uropepsina be added to the routine methods in our clinical laboratories.